The 6-GHz multibeam maser survey - II. Statistical analysis and Galactic distribution of 6668-MHz methanol masers - Green, J.; Breen, S.; Fuller, G.; McClure-Griffiths, N.; Ellingsen, S.; Voronkov, M.; Avison, A.; Brooks, K.; Burton, M.; Chrysostomou, A.; Cox, J.; Diamond, P.; et al. (Oxford University Press, 2017)
The Methanol Multibeam survey has produced the largest and most complete census of methanol and excited-state hydroxyl masers in the Galaxy to date. Observing the entire Galactic plane visible from the Southern hemisphere for 6668-MHz methanol and 6030/6035-MHz hydroxyl masers, to an rms sensitivity of 0.015 Jy km s−1, the survey has detected a total of 972 methanol maser sources, implying a total Galactic population of ~1290 sources with flux densities above the survey 3σ peak flux density limit of 0.51 Jy. We present here the statistical properties of the methanol detections of the survey, including distributions in flux density, variability and range of source velocities. The data suggest that the weaker masers exhibit greater variability. We also present an analysis of the Galactic distribution of 6668-MHz methanol masers. For the Galactic distribution, we present kinematic distance resolutions to an additional 202 sources to those published previously, and collate these with previous allocations, as well as exploring a recent Bayesian distance approach based on maser parallaxes to separately determine distances. We examine Galactic structure and determine the luminosity function of the Galactic population of methanol masers. We find that more luminous masers have an evenly distributed wide range of velocity widths compared with less luminous masers being dominated by narrow velocity ranges, with the implication that this may be tied to the evolution of the host protostar(s). We also see an indication that brighter sources are seen towards the arm origins.